Genome-wide identification and expression analysis of BrAGC genes in Brassica rapa reveal their potential roles in sexual reproduction and abiotic stress tolerance - Wu, Xiaoyu; Pan, Lianhui; Guo, Xinping; Li, Ting; Li, Jiali; Duan, Qiaohong; Huang, Jiabao (Frontiers in Genetics, 2022)
AGC protein kinases play important roles in regulating plant growth, immunity, and cell death. However, the function of AGC in Brassica rapa has not yet been clarified. In this study, 62 BrAGC genes were identified, and these genes were distributed on 10 chromosomes and divided into six subfamilies. Analysis of gene structure and conserved motifs showed that the activation segment of BrAGC genes was highly conserved, and genes of the same subfamily showed higher sequence and structural similarity. Collinearity analysis revealed that BrAGCs were more closely related to AtAGCs than to OsAGCs. Expression profile analysis revealed that BrAGCs were preferentially expressed in flowers and BrAGC26, BrAGC33, and BrAGC04 were preferentially expressed in the stigma; the expression of these genes was significantly upregulated after self-incompatibility pollination, and the expression of BrAGC13 and BrAGC32 was significantly upregulated after cross-pollination. In addition, several typical cis-elements involved in the stress response were identified in BrAGC promoters. The expression levels of BrAGC37 and BrAGC44 significantly varied under different types of abiotic stress. Collectively, we identified that BrAGC26, BrAGC33, and BrAGC44 have the greatest potential in regulating pollen-pistil interaction and abiotic stress tolerance, respectively. Our findings will aid future functional investigations of BrAGCs in B. rapa.